A dyadic analysis of undergraduate peer-mentoring relationships in the context of a formal peer-mentoring programme at a university residence - Bosman, Vincent Charles (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.